HOMOEOPATHIC MANAGEMENT OF AUTOIMMUNE DISEASES - A CASE SERIES ON PSORIASIS - DR. VEERABHADRAPPA C,; DR. KIRTIDA DESAI,; DR. POORAV DESAI, (The Bioscan, 2025)
Psoriasis is an autoimmune skin disease characterized by T cell-mediated hyperproliferation of keratinocytes. It is a longterm dermatological disorder that can adversely influence both physical health and mental well-being. We observed eight patients diagnosed with psoriasis who were managed with individualized Homoeopathic medicines selected on the basis of their characteristic presentations. Over the course of follow-up, all patients demonstrated steady clinical improvement. Longstanding lesions gradually became thinner, scaling was markedly reduced, and itching diminished significantly. Within a few months, the overall condition of each patient had improved without any adverse reactions being reported. In addition to the relief of skin symptoms, patients described enhanced general well-being, better quality of sleep, and greater confidence in their social interactions.